Предмет: Математика,
автор: tanyakolosova
найти корни уравнения: (х+1/6)(х-1/6)-(2х-11/36)=0
Ответы
Автор ответа:
1
(x+1/6)(x-1/6)-(2x-11/36)=0
x²-1/36-2x+11/36=0
x²-2x+10/36=0
x²-2x+5/18=0
D=(-2)² - 4*(5/18)=4 - (10/9)=26/9
x₁=2-√(26/9) = 2 - (√26)/3 = 6 - √26
2 2 6
x₂=6 + √26
6
x²-1/36-2x+11/36=0
x²-2x+10/36=0
x²-2x+5/18=0
D=(-2)² - 4*(5/18)=4 - (10/9)=26/9
x₁=2-√(26/9) = 2 - (√26)/3 = 6 - √26
2 2 6
x₂=6 + √26
6
Похожие вопросы
Предмет: Русский язык,
автор: Аноним
Предмет: Русский язык,
автор: fioletovaannap2alfs
Предмет: Окружающий мир,
автор: salll04ек
Предмет: Информатика,
автор: shupnevIvan
Предмет: Русский язык,
автор: Mashakazakova10